Past, present, and future of global health financing: a review of development assistance, government, out-of-pocket, and other private spending on health for 195 countries, 1995–2050 (2019)
Financial resources are an essential input to health systems—at a minimum, these are necessary to purchase medicines and supplies, build health facilities, and pay health workers. However, limited financial resources are a universal constraint faced by all health systems. WHO has identified health financing as one of the six key building blocks of health systems and adequate financing is essential to the other five blocks.1 Health financing systems are tasked not only with raising sufficient financial resources to fund the health system, but doing so in a way that promotes equity.2 Health systems funded according to one's ability to pay, such as those based on income taxes, promote both financial equity and better health.3 Over-reliance on out-of-pocket spending diminishes access to care for those who are uninsured or underinsured, and risks exacerbating the burden of ill health and increasing poverty due to the high cost of care.4 The recognised importance of financial protection has led to its inclusion as one of two pillars of universal health coverage, alongside coverage of core health services, as outlined in Sustainable Development Goal 3.